2021
DOI: 10.1108/itp-04-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the development stages of virtual teams – An application of social network analysis

Abstract: PurposeThe purpose of this study is to explore some quantitative indicators from the social network analysis, observe the variations of these indicators over time and determine whether these indicators fit into the traditional team development stages model or theory. The primary focus is on the perspective of social interaction rather than the suitability of the indicator, i.e. the authors will not determine the optimal indicators nor compare the performance of different indicators. This study aims to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…point out that the benefits of VPTs in terms of cost savings are clear and cannot be overlooked. Lin and Roan (2021) have confirmed that a successful virtual workforce assists businesses cut expenses while boosting output. Moreover, global virtual teams can avoid costly face-to-face contacts thanks to the growth of multinational virtual teams (MNVT) (Cheng et al, 2021;Zaharie, 2021).…”
Section: • Cost Reductionmentioning
confidence: 71%
See 4 more Smart Citations
“…point out that the benefits of VPTs in terms of cost savings are clear and cannot be overlooked. Lin and Roan (2021) have confirmed that a successful virtual workforce assists businesses cut expenses while boosting output. Moreover, global virtual teams can avoid costly face-to-face contacts thanks to the growth of multinational virtual teams (MNVT) (Cheng et al, 2021;Zaharie, 2021).…”
Section: • Cost Reductionmentioning
confidence: 71%
“…Moreover, companies could experience a rise in efficiency and effectiveness thanks to the chance to engage the finest employees in GVTs, regardless of where they are physically located (Capolupo et al, 2022). Other Researchers confirmed that, one of the benefits of global virtual teams is their ability to access larger pools of talent Lin & Roan, 2021). Because GVTs provide a number of advantageous outcomes, many international corporations employ them.…”
Section: Access To a Wider Pool Of Talentmentioning
confidence: 99%
See 3 more Smart Citations